A Case Study on Thailands New Teleprotection Regulation: Direct Transfer Trip Application in Distributed Generation Network - Naradon Chotiwanaporn; Chow Chompoo-Inwai (My University, 2017)
This research paper presents the new idea of applying the transmission line teleprotection scheme called direct transfer trip (DTT) technique to use with a closed-loop distribution network.A large-scale 163MW gas turbine power plant connected to a three-substation closed-loop distribution network was chosen to be a case study here.A newly-proposed DTT configuration, DTT logic diagram and circuit breaker trip matrix had been redesigned and presented in this paper.For the proposed DTT configuration, several remote terminal units will be installed at every substation connected to the distribution network, whereas the logic controller will be installed at the selected power plant.A huge advantage over the conventionally-installed zoning peer-to-peer protection scheme is that the proposed DTT logic controller is able to almost instantaneously compute and send out the clearing faults command, regardless of fault locations in this particular closed-loop distribution network, while the conventional one cannot in many cases.Additional benefit is that the proposed DTT teleprotection scheme completely prevent the generators from operation in island mode resulting in minimal lost and damages caused from this circumstance.The relay test tool is used to verify the proposed DTT protective capabilities and speed.The simulation and commissioning test results confirm the proper functionality of the proposed technique.The implementation to the real field has been done and presented here as well.What we have learned from this case study shall be a very good guideline for other similar circumstances.
Keywords: Power Systems Fault Detection